Australia : land of natural wonders - Ruiz de Larramendi, Alberto (Chicago : Childrens Press, 1994)
Surveys all the areas in Australia that UNESCO has declared World Heritage sites.
Includes index.
7.2
3-12.
5-8
Keywords: Natural history -- Australia -- Juvenile literature; Natural history -- Australia; Natural history -- Australia